E-commerce Marketplace Penjualan Terasi: (Studi Kasus : PT. Pabrik Terasi Sejahtera Sungi Lumpur Tulung Selapan) - Helda Yudiastuti; Irwansyah Ibrahim; Ade Putra; Akhmad Khudri (Jurnal Ilmiah Matrik, 2026)
PT. Pabrik Terasi Sejahtera is a shrimp paste (or calok) factory located in the Sungai Lumpur Tulung Selapan area of ​​Ogan Komering Ilir Regency, South Sumatra. Its sales and promotions are still carried out manually, relying solely on land transportation to distribute or market sales to nearby stores. Currently, the company wishes to introduce and develop shrimp paste marketing by expanding its shrimp paste marketing area beyond the region. To address this issue, the researcher will build an Ecommerce Marketplace (E-Marketplace). The research method used in this study is a qualitative method. While the system development method used in this study uses the Prototype Method. The results of this study are in the form of an Ecommerce Marketplace Application for shrimp paste sales. With this E-Marketplace, the company can more easily expand its shrimp paste product marketing area, more easily promote its shrimp paste products, so that the public is more familiar with the various shrimp paste products produced by PT. Pabrik Terasi Sejahtera.